Association between antithrombotic treatment and hemorrhagic stroke in patients with atrial fibrillation—a cohort study in primary care - Wändell, Per (Eur J Clin Pharmacol, 2016)
OBJECTIVE: The objective of this study was to study the association between antithrombotic treatment and risk of hemorrhagic stroke (HS) in patients with atrial fibrillation (AF) treated in primary health care. METHODS: Study population included all adults (n = 12,215) 45 years and older diagnosed with AF at 75 primary care centers in Sweden 2001–2007. Outcome was defined as a first hospital episode with a discharge episode of HS after the AF diagnosis. Association between HS and persistent treatment with antithrombotic agents (warfarin, acetylsalicylic acid (ASA), clopidogrel) was explored using Cox regression analysis, with hazard ratios (HRs) and 95 % CIs. Adjustment was made for age, socioeconomic status, and co-morbid cardiovascular conditions. RESULTS: During a mean of 5.8 years (SD 2.4) of follow-up, 162 patients (1.3 %; 67 women and 95 men) with HS were recorded. The adjusted risk associated with persistent warfarin treatment compared to no antithrombotic treatment consistently showed no increased HS risk, HR for women 0.53 (95 % CI 0.23–1.27) and for men 0.55 (95 % CI 0.29–1.04); corresponding HRs for ASA were, for women, 0.45 (95 % CI 0.14–1.44) and, for men, 0.56 (95 % CI 0.24–1.29). CONCLUSIONS: In this clinical setting, we found no evidence pointing to an increased risk of HS with antithrombotic treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00228-016-2152-8) contains supplementary material, which is available to authorized users.